2019
DOI: 10.1029/2019wr024701
|View full text |Cite
|
Sign up to set email alerts
|

Future Trends in the Interdependence Between Flood Peaks and Volumes: Hydro‐Climatological Drivers and Uncertainty

Abstract: Reliable flood estimates are needed for designing safe and cost-effective flood protection structures. Classical flood estimation methods applied for deriving such estimates focus on peak discharge and neglect other important flood characteristics such as flood volume and the interdependence among different flood characteristics. Furthermore, they do not account for potential nonstationarities in hydrological time series due to climate change. The consideration of both the interdependence between peak discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Regime changes are caused by changes in precipitation seasonality and intensity (Brönnimann et al, 2018) and seasonal shifts and decreases in melt contributions (Farinotti et al, 2016;Jenicek et al, 2018) related to reduced snow and glacier storage (Beniston et al, 2018). Predicted regime changes are relatively robust (Addor et al, 2014) compared to changes in high and low flows, which are highly uncertain (Brunner et al, 2019c;Madsen et al, 2014) because of diverse uncertainty sources introduced in various steps along the modeling chain (Clark et al, 2016). It has been shown that future regime changes can be linked to changes in flood and drought characteristics, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Regime changes are caused by changes in precipitation seasonality and intensity (Brönnimann et al, 2018) and seasonal shifts and decreases in melt contributions (Farinotti et al, 2016;Jenicek et al, 2018) related to reduced snow and glacier storage (Beniston et al, 2018). Predicted regime changes are relatively robust (Addor et al, 2014) compared to changes in high and low flows, which are highly uncertain (Brunner et al, 2019c;Madsen et al, 2014) because of diverse uncertainty sources introduced in various steps along the modeling chain (Clark et al, 2016). It has been shown that future regime changes can be linked to changes in flood and drought characteristics, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In literature there are several methods used to select a flood event (e.g., [51][52][53][54] ). Among these, here, we have chosen a simple method based on a discharge threshold, a fixed percentile of daily discharge, also adopted in 18,32,51,53,[55][56][57] . The beginning and end of a flood event are respectively the first and last value, when the discharge is greater or equal the threshold.…”
Section: Dataset and Flood Events Samplingmentioning
confidence: 99%
“…Vezzoli et al 29 used the pairwise dependence in order to assess the performance of climate-hydrology models. Some studies have investigated the possible non-stationarity of such dependencies 30 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous univariate and bivariate flood risk assessments assume the missing flood characteristic to be the long‐term, historical average and be independent of other characteristics considered, leading to overestimation or underestimation of flood risks (Alfieri et al., 2017; Balistrocchi et al., 2017). Thus, it is desired to explore the interdependence among flood characteristics, and multivariate approaches have received great attention in recent years (Brunner et al., 2019; Quinn et al., 2019; Santhosh & Srinivas, 2013). As one of the most popular multivariate approaches, copula has been extensively used to assess the dependence structure of flood characteristics and to estimate the return period of floods (Favre et al., 2004; Jeong et al., 2014; Mallakpour et al., 2019; Moftakhari et al., 2017).…”
Section: Introductionmentioning
confidence: 99%